Sistem Jaringan Small Office Home Office (Soho) Menggunakan Mikrotik - Ira Zulfa; Hendri Syahputra; M. Abdul Rahim; Fajrillah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
A computer network system is defined as a collection of several independent computers connected to each other. This connection allows these computers to share information and programs with each other (Putuasduki, 2021). SOHO stands for Small Office, Home Office. SOHO is a hybrid apartment between residential and commercial space, where people can work and live in the same building. SOHO apartments are typically loft style, meaning they have high ceilings. High ceilings lend themselves well to building a mezzanine, an elevated area accessible by stairs that can be used as a bedroom or desk. (Armee et al., 2022). Mikrotik is a software-based operating system that turns a computer into a network router (Gamaliel and Arliyanto, 2022). This operating system is ideal for managing computer networks, such as building large or small computer network systems. (Putra et al., 2020). Gajah Putih University Faculty of Engineering always needs a very large network connection. In addition, many students use an internet connection. Difficulties in optimizing network use and equalizing bandwidth between students and faculties, internet network problems and difficulties in monitoring network users at the Gajah Putih Faculty of Engineering and students still asking for web searches off campus are the biggest problems. this lesson. For that we need a learning environment that can support the learning process in the field of computer networks. This study discusses learning media to build computer networks in small offices and home offices by using a proxy server, starting from the basic concept of computer networks so that the network can function properly. Network Development Life Cycle Model (NDLC). Flow Network Development Lifecycle Diagram Continuous process analysis is a step by step process that describes the journey of data or documents through ongoing processes in all research locations. The network topology that was operated at the Faculty of Engineering, University of Gajah Putih before using a proxy server is shown in Figure 2. Meanwhile, the network topology that was operated before using a proxy server in the laboratory of the Faculty of Engineering, University of Gajah Putih can be determined from the results of research and design of the home office network of the Faculty of Engineering, Gajah Putih University Using a proxy allows it to be concluded that with the help of the home office network of the Faculty of Technology, University of Gajah Putih using a proxy server technically students can easily access the internet for free and the signal in the university building can be easily closed. The security system used in this wireless network (base station) is implemented on the server. Therefore, if you want to use the Internet, the user must enter a username and password. This network uses a DHCP server so that the server distributes IP addresses as wide as possible resulting in long loading times when many users are active. Sharing Internet bandwidth with a proxy server enables efficient use of Internet bandwidth. By using a proxy server with Winbox, IT administrators can perform network configuration more easily.